Social-Economic Diversification for Urban Decision Makers. Case study: Regions of Ukraine - Соколова, Л. В.; Манакова, Н. О.; Колісник, О. В. (ФОП Вишемирський В.С., 2019)
The analysis of the regional diversification is essential for stakeholders as urban decision makers and it is also an important question whether the inequalities are growing or decreasing. Economic and social differences in the development of districts/cities/regions encourage finding new tools for their development that would lead to assessment and implementation of global and local goals. In the paper, the emphasis was made on the evaluation of indicators of social- economic development of Ukrainian regions and revealing inequalities as a case study. The aim of this paper is to identify similar or identical characteristics of each region using mathematical and statistical methods by means of indicators relating to the income situation of households and highlight dependencies between the examined indicators. Similarities of the regions will be expressed using clusters into which they are divided.
Keywords: diversification; regional diversification; system of indicators; socio-economic characteristics; socio-economic diversification; urban decision makers